The Little Puppy - Killen, Nicola (New York : Simon & Schuster Books for Young Readers, 2024)
When a play date with Grandma's new puppy Milo does not go as planned, Ollie finds a way to still have fun.
Keywords: Puppies -- Juvenile fiction; Animals -- Juvenile fiction. -- Infancy; Play -- Juvenile fiction; Dogs -- Fiction; Animals -- Fiction. -- Infancy; Play -- Fiction; Picture books